HYDROLOGICAL EVALUATION OF RADIOACTIVE WASTE DISPOSAL SITE AT IPEAN: STUDY OF MOVEMENT OF SOIL MOISTURE AND GROUND WATER RECHARGE BY ARTIFICIAL TRITIUM TAGGING METHOD - CHANDRA, UMESH; POLI, DORA DE CASTRO RUBI (Águas Subterrâneas, 1980)
RESUMO NÃO DISPONIVEL